2011
DOI: 10.1190/1.3672483
|View full text |Cite
|
Sign up to set email alerts
|

Rock physicists step out of the well location, meet geophysicists and geologists to add value in exploration analysis

Abstract: A primary task for a petroleum rock physicist is to link geological and geophysical interpretation practices and culture in such a way that they can be understood and applied in exploration and production of oil and gas. Specifically, this task asks for relations between key properties of the fluid-saturated rocks located in situ and quantities extracted from seismic and electromagnetic data. In spite of the hard work needed to establish a proper characterization of such relations, they are of limited if not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Per Avseth 1, 2 and Ivan Lehocki 3 Helset et al (2004) were the first to combine kinetic modeling of quartz cementation and associated porosity evolution, introduced by Walderhaug (1996), with rock-physics modeling using contact cement theory by Dvorkin and Nur (1996). Brevik et al (2011), Draege et al (2014), and Avseth et al (2014) further showed how burial history can be combined with rock physics to improve the understanding of seismic signatures in areas with complex tectonics or in frontier areas with limited well control. In this study, we utilize this integrated approach to predict sandstone texture and associated seismic properties as a function of geologic time for a North Sea case and a Barents Sea case.…”
Section: Introductionmentioning
confidence: 99%
“…Per Avseth 1, 2 and Ivan Lehocki 3 Helset et al (2004) were the first to combine kinetic modeling of quartz cementation and associated porosity evolution, introduced by Walderhaug (1996), with rock-physics modeling using contact cement theory by Dvorkin and Nur (1996). Brevik et al (2011), Draege et al (2014), and Avseth et al (2014) further showed how burial history can be combined with rock physics to improve the understanding of seismic signatures in areas with complex tectonics or in frontier areas with limited well control. In this study, we utilize this integrated approach to predict sandstone texture and associated seismic properties as a function of geologic time for a North Sea case and a Barents Sea case.…”
Section: Introductionmentioning
confidence: 99%
“…The rock-physics model follows mechanical and chemical compaction laws when modeling the porosity and anisotropic or isotropic stiffness components from which properties such as P-and S-wave velocities, anisotropy, and density are calculated. The rock model is universally calibrated to various depositional and geohistory sets from hundreds of wells worldwide (Brevik et al, 2011), and the only parameterization needed is for lithology type and depositional attributes. Access to well-log data (also for better lithology and depositional attribute definition) helps to build confidence in the produced velocity and density fields.…”
Section: Rock-physics Modelingmentioning
confidence: 99%
“…The estimated models are, however, nonunique because several "earth models" may fit the measured data (Bakulin et al, 2010). Recently, rock-physics modeling has been proposed as an additional source of information in the derivation of the anisotropic subsurface response (Bachrach et al, 2010(Bachrach et al, , 2011Brevik et al, 2011). Li et al (2011) and Helgesen et al (2013) show further how rock-physics constraints could be used in combination with seismic data to better address the nonuniqueness problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial velocity and anisotropy models for anisotropic imaging are then constructed by guided interpolation/extrapolation of the estimated parameters at well locations throughout the full volume (Bakulin et al, 2009). It was shown that the incorporation of geo-history can be used to predict seismic velocities using rock physics modelling (Brevik et al, 2011). We call the use of basin modelling simulations with rock physics to predict elastic attributes which can be used for anisotropic velocity model building or AVO as Geophysical Basin Modelling (GBM).…”
Section: Introductionmentioning
confidence: 99%